Maternidades: os repertórios interpretativos utilizados para descrevê-las - Moreira, Renata Leite Cândido de Aguiar (2009)
Although the first years of motherhood is placed as a critical period in the life of the woman, little assistance is directed her in this phase, being the child or biological questions the focus of the attention of the actions of the public health, as well as of great part of the academic productions. In this study, we understand the motherhood as a construction that involves multiples factors and we also consider the influence that the social speeches supported in the production of a concept of motherhood and the standardization of the ways to live it. The present study, inspired by the constructionist perspective, intended to contribute to the promotion of reflection about the socially descriptions available on being a mother and a woman. In this sense, the aim of this study was to describe the interpretative repertoires about the motherhood used by women who lives motherhood experience. We interviewed twelve mothers, among 18 and 36 years old who take part of a maternal and child Care Center, whose children were between 4 months and 14 years old, that the youngest child was between 4 months and 2 years old. The construction of the corpus was performed from the use of semistructured individual interviews, which in addition, allowed us a greater freedom for the interviewer to address the issues of interest as they arise in the conversation, and it helped us to rescue personal ways of developing concepts around motherhood. The analyses were performed according to discursive analysis influenced by social constructionist perspective, emphasizing the notion of interpretative repertoires. After the transcription of all interviews, there was a curious and reflective reading, enabling the identification and analysis of interpretative repertoires. The analysis of the repertoires had enabled us to identify some functions of its use, and its moral implications. Through analysis, we identified that participants described motherhood using four basics repertoires, which we named as (1) romantic motherhood , which is characterized by descriptions that put motherhood as a natural, full and incommunicable phenomenon; (2) medicated motherhood , in which motherhood is presented by a medical and psychological vocabulary; (3) exigent motherhood in which descriptions emphasize the demands in the exercise of being mother and (4) learning with the motherhood , through which motherhood is described as an opportunity for learning and changing. We observed that when such repertoires were used, the participants tried to put themselves as good mothers, seeking a comfortable place and a positive assessment in the interaction. We believe that this study had enabled us to identify the repertoire and to analyze the elements in those sets, also had allowed us to create a moment for reflection about the meanings of motherhood. And thus, this study highlighted the importance of professionals doctors, nurses, psychologists, educators, researchers and the society in general being sensitive to interpretative repertoires socially available which can expand or limit the possibilities of meaning around motherhood, and often serve to maintain oppressive discourses and practices for people men and women, mothers and not mothers.